Attitudes and patterns of alcohol consumption among trisikad drivers in Barotac Nuevo, Iloilo. - Dimafiles, Jesus C
This descriptive study was conducted to describe the patterns of alcohol consumption and attitude towards alcohol drinking of the members of Zamora Trisikad Operators and Drivers Association (ZATODA), Ilaud Poblacion, Barotac Nuevo, Iloilo. The study has the following objectives: (1) to describe the patterns of alcohol consumption of trisikad drivers; (2) to describe their motivations for drinking, and attitudes regarding alcohol consumption; and (3) to examine if there are differences in drinking patterns, motivations and opinions regarding alcohol consumption of drivers by their characteristics. All the 30 trisikad drivers of ZATODA were made respondents. The attitudes and patterns of alcohol consumption of the drivers were compared across their different characteristics (such as age, marital status, education and status in the household). The study was conducted in the municipality of Barotac Nuevo, Iloilo. Results showed that all the participants tried drinking alcohol beverages. Majority (90.0%) of the participants are currently drinking. More than half (55.6%) of the current drinkers drink daily/almost daily and about 44% are not drinking everyday. Out of the current drinkers (55.6%) are normal drinkers and few are not. Most of the drivers are motivated to drink for enjoyment and relaxation. They are willing to accept suggestions from family and friends about their drinking. Frequency of alcohol consumption, motivations and opinions regarding alcohol consumption varied significantly by age, marital status and household status of the drivers.